Ozonated Olive Oil: Enhanced Cutaneous Delivery via Niosomal Nanovesicles for Melanoma Treatment - Sherif Ashraf Fahmy; Asmaa Ramzy; Amany M. Sawy; Mohamed Nabil; Mohamed Z. Gad; Mohamed El-Shazly; Mourad A. M. Aboul-Soud; Hassan Mohamed El-Said Azzazy (Antioxidants, 2022)
Ozonated olive oil (OL) combines the therapeutic effects of both ozone and olive oil. However, it suffers from limited water solubility and poor transdermal permeation, which hinder its application in melanoma treatment. Nanocarrier host molecules, such as niosomes, were used to improve the water solubility, transdermal permeation, and anticancer effect of hydrophobic compounds. This study aims to design and optimize a niosomal vesicular nanoplatform loaded with OL (OL/NSs) to improve OL’s skin permeation and anti-melanoma effect. In this regard, OL was prepared and characterized by evaluating its chemical properties (acid, peroxide, and iodine values) and fatty acid composition using gas chromatography. Then, OL/NSs were developed using the thin film hydration method employing cholesterol, Span 60, and Tween 60 at five different molar ratios. The optimized niosomes had an average diameter of 125.34 ± 13.29 nm, a surface charge of −11.34 ± 4.71 mV, and a spherical shape. They could entrap 87.30 ± 4.95% of the OL. OL/NSs showed a 75% sustained oil release over 24 h. The skin permeation percentage of OL/NSs was 36.78 ± 3.31 and 53.44 ± 6.41% at 12 and 24 h, respectively, three times higher than that of the free OL (11.50 ± 1.3 and 17.24 ± 2.06%, at 12 and 24 h, respectively). Additionally, the anticancer activity of the developed niosmal formulation, when tested on human melanoma cells (A375), was double that of the free OL; the IC50 of the OL/NSs was 8.63 ± 2.8 μg/mL, and that of the free OL was 17.4 ± 3.7 μg/mL. In conclusion, the encapsulation of ozonated olive oil in niosomes enhanced its water solubility, skin permeation, and anticancer activity and thus may represent potent natural chemotherapy in treating melanoma.